Energy, exergy and techno-economic analyses of hydrothermal oxidation of food waste to produce hydro-char and bio-oil. (1st May 2016) - Mahmood, Russell; Parshetti, Ganesh K.; Balasubramanian, Rajasekhar
Abstract: In this study, energy, exergy and techno-economic analyses of HOT (hydrothermal oxidation) of food waste to solid (hydrochar) and liquid (bio-oil) fuels were performed. The HOT process was carried with and without enzymatic pre-treatment for fuel production. A conceptual chemical mass balance model was developed. Increasing the process temperature increased the yield of bio-oil and enhanced the quality of the hydro-char. Inclusion of the enzymatic pre-treatment reduced bio-oil yield but enhanced hydro-char quality. Energy balance and exergy analyses indicated that the HOT process is feasible at different operating temperatures. However, the energy conversion efficiencies of the process decreased with increasing temperatures. TEA (Techno-economic analysis) was performed to assess economic feasibility. The "minimum selling price" of products was calculated and compared with the existing market prices. Finally, a sensitivity analysis was carried out, which showed that the price of bio-oil and enzymes had the highest impact on the profitability of the plant in the case of the enzymatic pre-treated process while the bio-oil yield had the highest impact for the non-enzymatic process. Monte-Carlo simulation was carried out to examine the robustness of TEA analysis. Graphical abstract: Highlights: A techno-economic assessment of HOT for food waste was performed. The HOT process is energetically favorable. The efficiency of the HOT process decreases with increasing temperature. The enzymatic pre-treatment improves quality of products, but at a higher price. Minimum selling" prices of fuel products were calculated.